Analisis Pengaruh Produk, Harga, dan Promosi terhadap Kepuasan Konsumen Gula Jahe Alami Sucenjurutengah - Suhartini, Titik (JURNAL AKUNTANSI DAN MANAJEMEN, 2025)
This study aims to determine the simultaneous ef ect of product, price, and promotion on consumer satisfaction with Natural Ginger Sugar, and the partial ef ect of product, price, and promotion on consumer satisfaction with Natural Ginger Sugar. The sample size was 40 respondents. The sample selection technique used was purposive sampling. The instrument was tested using validity, reliability, and heteroscedasticity. The data analysis technique used was multiple linear regression analysis using IBM SPSS 24. The results of this study indicate that: Product has a positive but insignificant efect on consumer satisfaction with Natural Ginger Sugar. The t-test data for the product variable indicates that the product has no significant partial effect on consumer satisfaction. Price has a positive and significant effect on consumer satisfaction with Natural Ginger Sugar. The t-test data for the price variable indicates that price has a partial and significant ef ect on consumer satisfaction, and promotion has a positive and significant effect on consumer satisfaction with Natural Ginger Sugar. The t-test data for promotion indicates that promotion has no partial ef ect on consumer satisfaction. The f-test results indicate that product, price, and promotion simultaneously influence consumer satisfaction.